Microwatt volatile optical bistability via nanomechanical nonlinearity - Papas, Dimitrios (2023)
Metastable optically controlled devices (optical flip-flops) are needed in data storage, signal processing, and displays. Although nonvolatile memory relying on phase transitions in chalcogenide glasses has been widely used for optical data storage, beyond that, weak optical nonlinearities have hindered the development of low-power bistable devices. This work reports a new type of volatile optical bistability in a hybrid nano-optomechanical device, comprising a pair of anchored nanowires decorated with plasmonic metamolecules. The nonlinearity and bistability reside in the mechanical properties of the acoustically driven nanowires and are transduced to the optical response by reconfiguring the plasmonic metamolecules. The device can be switched between bistable optical states with microwatts of optical power and its volatile memory can be erased by removing the acoustic signal. The demonstration of hybrid nano-optomechanical bistability opens new opportunities to develop low-power optical bistable devices.